Meaningful Economic Entrepreneurship: Evolution of Business Ethics, Existential Positioning and Customer Connectivity - Junedi Junedi; R. R. Wening Ken; Ida Abdul Gopar (Jurnal Ar Ro'is Mandalika (Armada), 2025)
This study aims to analyze the influence of the evolution of entrepreneurial ethics, existential position, and customer connectivity on meaningful economic entrepreneurship in SME’s entrepreneurs. In the pattern of changing consumer behavior and demands for more ethical business, entrepreneurs need to build strong relationships, meaningful values, and an image that is trusted by the public. This study uses a quantitative approach with a survey method on 85 SME’s entrepreneurs in Bekasi, West Java. The data was analyzed using multiple linear regression tests to see the extent to which independent variables affect meaningful economic entrepreneurship as dependent variables. The results show that the evolution of entrepreneurial ethics, existential position and customer connectivity have a positive and significant effect on meaningful economic entrepreneurship. Customer connectivity makes a dominant contribution to creating value and loyalty. This study suggests that SME’s integrate ethical principles, emotional relationships and clarity of business identity in business strategies in order to achieve long-term sustainability.